Implementasi Pendidikan Karakter dalam Perspektif di Sekolah - Tutuk Ningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Character education requires a basis of conceptualization of the character and moral comprehensively by cultural basis which is clear and focused. To form students who have a positive character, it should also require the environment which has character. Person’s behavior is determined by the environment it means someone is going to be a person who has character if grown in environments characterized. That’s what needs to be built the basic character which is from the moral values of humanity in the community, both as individuals or groups. Education establishes good character and personality intact someone, besides every parent in the family, it can also be done through moral guidance in schools, moral guidance should be designed and managed in such a way so that in the learning process there is also the process of establishing good attitudes and behavior, in practising character values can be taught through activities intracurricular (integrated subjects) and extracurricular activities so that students can translate in real behavior. Character education is everything is done by the teacher, which could affect the character of students. Teacher helps forming the character of students. This includes how the implementation of exemplary character education in the perspective at schools especially teacher behavior, the way teachers speak or deliver material, how teacher tolerates and other related matters. Character education is an investment system of values character to the citizens of the school which includes the components of knowledge, awareness or volition/ will, and action to implement those values. Implementation can be realized through the methods: (1) know how to lose, (2) understand the difference between winning and success, (3) respect for others, (4) work with others, (5) demonstrated integrity, (6) show self-confidence, and, (7) give return. Keywords: Implementation, character education, school